QRIS IN INDONESIA: A COMPREHENSIVE LITERATURE REVIEW ON ADOPTION, CHALLENGES, AND OPPORTUNITIES - Prawitasari, Dian; Badiani, Farah Dina; Rachmawati, Syafalia Dewi; Ningrum, Febyana Puspita; Mufidah, Nabila Lutfi (REVENUE: Jurnal Manajemen Bisnis Islam, 2024)
Indonesia grapples with multifaceted challenges in the adoption of digital payment systems, marked by regulatory ambiguities, inadequate financial literacy, and organizational intricacies. Despite strides in technological innovation, the nation's readiness for widespread digital payment adoption remains uncertain. To address these complexities, concerted efforts are imperative. Enhancing financial literacy among the populace emerges as a foundational step, empowering individuals to navigate the digital financial ecosystem effectively. Moreover, fostering collaborative partnerships between regulatory bodies, financial institutions, and private enterprises is crucial to surmounting regulatory hurdles and fostering innovation. Recommendations include refining regulatory frameworks to provide clarity and flexibility, instituting comprehensive financial education programs, and incentivizing private sector involvement in digital payment initiatives. By embracing these strategies, Indonesia can overcome the complexities of digital payment adoption, unlocking the potential for inclusive economic growth and financial empowerment across diverse societal segments.